Recent Developments Studies on Wood Protection Research in Academia: A Review - Khademibami, Laya; Bobadilha, Gabrielly S. (Frontiers in Forests and Global Change, 2022)
In this review, using natural compounds and preservatives in new engineered wood products, developing new products to be replaced in inorganic oil-based preservatives, and achievements of different types of wood modification have been studied. These days, reduction in use of non-renewable resources is a crucial concern. Wood and wood-based products are generally low in CO2 emissions and can be gained from sustainable forest resources. Therefore, they can play a significant role as renewable resources. In comparison to other building materials, wood has numerous advantages, such as suitable thermal insulation, high strength to weight ratio, easy machinability, and attractive aesthetics. Wood as a valuable building and industrial material requires to be protected due to its biodegradable properties when used in highly hazardous applications to improve the properties of service life of wood. Wood durability can be improved through wood protection which include wood preservatives and modification systems. Wood protection should be safe to use, efficient, cost-effective, permanent, and should not corrode metal or degrade wood components. Numerous reviews of wood protection are to be found in the scientific literatures, but until now a review of a combination of wood preservation and wood modification has not been studied. This paper presents an overall summary of the recent developments on wood preservatives, different types of preservatives, natural preservative compounds, and modification technologies.